Penerapan Metode TOPSIS & SAW Dalam Pemilihan Destinasi Wisata Di Jawa Timur - Irfan Mahendra; Adynoto Suprapto (INFORMAL: Informatics Journal, 2020)
This research was conducted to test the application of the Technique Order Preference by Similarity to Ideal Solution (TOPSIS) method and the Simple Additive Weighting (SAW) method in the decision-making process of choosing tourist destinations in East Java. This research is motivated by the problems faced by the Jakarta Backpacker Community who often have difficulty in making choices about tourist destinations to be visited in East Java. The criteria used in this study are cost, destination, meeting point, trip length and facilities obtained. The results of this study indicate that The TOPSIS method and the SAW Method can be used for the decision-making process in the selection of tourist destinations in East Java, with the results of Explore Baluran and Menjangan being the most recommended choices as the primary choice. Besides, it is also known that there is a match between the TOPSIS and SAW methods, with the calculation results using the TOPSIS method that is 0.64 and the calculation using the SAW method is 0.86 as the highest calculated value. So as such, these two methods can be stated equally well used in the process of determining tourist destinations in East Java. However, this applies only to the highest value, because for the order of two and so on, the results of calculations on these two methods show differences in rank.